Vibrational characteristics of iVAC and three ultrasonic metallic inserts: analysis by laser Doppler vibrometry - Hermano Camelo PAIVA; Eduardo AKISUE; Marco Antônio Húngaro DUARTE; George Táccio de Miranda CANDEIRO; Marcílio ALVES; Giulio GAVINI (Brazilian Oral Research)
Abstract The iVAC system combines ultrasonic activation with negative-pressure irrigation, highlighting the importance of determining its vibration characteristics. This study aimed to evaluate the oscillation characteristics of the iVAC system using laser Doppler vibrometry and to compare them with those of metallic inserts used for ultrasonic irrigation. Four ultrasonic inserts—Irrisonic, Nitisonic, Ultra X Blue, and iVAC—were attached to an ultrasonic unit, secured in a holder, and operated at a power setting of 15%. A laser scanning vibrometer was used to scan the first four millimeters of each insert. Each measurement, lasting approximately 20 seconds, was repeated ten times per insert and performed at millimeter intervals. Displacement amplitude and frequency data were recorded for each insert. Furthermore, scanning electron microscopy was employed to evaluate the surface finish of the inserts, and their elemental compositions were analyzed using energy-dispersive X-ray spectroscopy (EDS). Analysis of variance and Tukey’s test were conducted to compare the performance of the inserts. The displacement amplitudes showed significant differences between inserts and among the scanned points (p < 0.05). All inserts demonstrated ultrasonic vibration frequencies exceeding 20 kHz. EDS analysis revealed that the elemental composition of the E1-Irrisonic tips was consistent with stainless steel. In contrast, the Nitisonic insert displayed a chemical composition characteristic of an equiatomic nickel–titanium (NiTi) alloy, whereas the Ultra X Blue insert contained additional elements beyond NiTi. The characteristics and composition of ultrasonic inserts significantly influence their displacement amplitude and vibration frequency. At the tested activation power, the iVAC insert, made of the organic thermoplastic polymer polyether ether ketone (PEEK), demonstrated an ultrasonic vibration pattern but exhibited the lowest oscillation amplitude among the inserts.